2021
DOI: 10.1007/s12350-020-02307-w
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibroblast activation detected by Ga-68 FAPI PET imaging as a potential novel biomarker of cardiac injury/remodeling

Abstract: Background Fibroblast activation protein (FAP) as a specific marker of activated fibroblasts can be visualized by positron emission tomography (PET) using Ga-68-FAP inhibitors (FAPI). Gallium-68-labeled FAPI is increasingly used in the staging of various cancers. In addition, the first cases of theranostic approaches have been reported. In this work, we describe the phenomenon of myocardial FAPI uptake in patients who received a Ga-68 FAPI PET for tumor staging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 23 publications
0
58
0
Order By: Relevance
“…SSTR-directed PET was also shown to be superior over 67 Ga-scintigraphy for identification of muscle, lymph node, and uvea lesions in a study including 20 patients with sarcoidosis [15]. Subsequent pilot studies examining cardiac sarcoidosis confirmed superiority of SSTR-directed PET vs. 18 F-FDG PET as well as a close correlation of results from cardiac magnetic resonance imaging (CMR) and SSTR-directed PET/CT [16,17].…”
Section: Somatostatin Receptorsmentioning
confidence: 90%
See 1 more Smart Citation
“…SSTR-directed PET was also shown to be superior over 67 Ga-scintigraphy for identification of muscle, lymph node, and uvea lesions in a study including 20 patients with sarcoidosis [15]. Subsequent pilot studies examining cardiac sarcoidosis confirmed superiority of SSTR-directed PET vs. 18 F-FDG PET as well as a close correlation of results from cardiac magnetic resonance imaging (CMR) and SSTR-directed PET/CT [16,17].…”
Section: Somatostatin Receptorsmentioning
confidence: 90%
“…Recently, Siebermair et al retrospectively analyzed 68 Ga-FAPI-PET images for cardiac tracer uptake of 32 patients that initially underwent PET analysis for tumor staging. The authors found an association with coronary artery disease (CAD), age, and left ventricle ejection fraction (LVEF) with FAPI uptake [67]. 68 Ga-FAPI in various inflammatory conditions.…”
Section: Fibroblast Activation Protein-α (Fap)mentioning
confidence: 99%
“…Switching the radioisotope, following in the footsteps of prostate-speci c membrane antigen radiopharmaceuticals, could grant a better resolution, other than facilitating the commercial distribution of this tracer. [25]; it could serve as a biomarker, working in synergy with the well-established cardiovascular prognostic risk factors [29], and it might have a role to assess treatment-related cardiotoxicity [35]. In rheumatological studies, [ 68 Ga]Ga-FAPI proved to complement [ 18 F]FDG information targeting brosis and in ammation, respectively [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…One study was designed as a phase I investigation [24]. In 12/23 studies [ 68 Ga]Ga-FAPI was offered as a compassionate drug according to the German Medicinal Product Act § 13(2b) [25,26,35,36,[27][28][29][30][31][32][33][34]. In the remaining 10/23 papers, the trial phase was not speci ed or designated as "not applicable" [37][38][39][40][41][42][43][44][45][46].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…7 Further retrospective evaluations of cardiac FAPI distribution in a heterogeneous patient population with metastasized cancer associated with preexisting coronary artery disease, cardiovascular risk factors or metabolic disease were reported. 8,9 However, 68 Ga-FAPI-04-PET investigations in patients after MI have not been reported yet. For this case presentation, we retrospectively evaluated fibroblast activation in a patient after MI und carcinoma patients without cardiac disease.…”
Section: Introductionmentioning
confidence: 99%